2015
DOI: 10.1016/j.ramd.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an exercise intervention on fatigue and sleep quality in midlife women: the FLAMENCO project

Abstract: Objective. Menopause is characterized by the presence of emotional instability and greater dissatisfaction with life. Therefore, we aimed to analyze the effects of an exercise intervention on quality of life and optimism in perimenopausal women.Method. Fourteen perimenopausal women (54.1 ± 3.2 years) participated in a 9 weeks (60 minutes/session, 3 days/week) moderate-vigorous intensity (12-16 rating of perceived effort) exercise intervention (aerobic and resistance exercise mainly).Health-related quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Seventy-eight university students were recruited for the present study. Students who met the following criteria were included: (1) had no prior exercise habits; (2) reported a Pittsburgh Sleep Quality Index (PSQI) score higher than seven, indicating poor sleep quality [19]; (3) had no diseases or hypoglycemic symptoms; (4) were not taking any medication; and (5) were not in their menstrual period if they were female.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventy-eight university students were recruited for the present study. Students who met the following criteria were included: (1) had no prior exercise habits; (2) reported a Pittsburgh Sleep Quality Index (PSQI) score higher than seven, indicating poor sleep quality [19]; (3) had no diseases or hypoglycemic symptoms; (4) were not taking any medication; and (5) were not in their menstrual period if they were female.…”
Section: Participantsmentioning
confidence: 99%
“…Among Chinese university students, this can also be attributed to academic workload and employment concerns [18]. Previous studies have shown that exercise interventions can be bene cial for sleep issues [2,5,11].…”
Section: Introductionmentioning
confidence: 99%